Impact of Hydroponic Oxygen Control in Sulfide Toxicity to Early Life Stages of Wild Rice (Zizania palustris). (29th January 2020) - Fort, Douglas J.; Mathis, Michael B.; Anderson, Kurt; Beranek, Rob
Abstract: Low‐headspace oxygen was used in the hydroponic design to evaluate the toxicity of sulfide to wild rice ( Zizania palustris ). Oxygen levels in the headspace gas phase were maintained at <0.005 atm. The results indicated that mesocotyl emergence was the most sensitive endpoint (≥3.1 mg/L sulfide and 0.8 mg/L iron [Fe]). At 2.8 mg Fe/L, ≥7.8 mg/L sulfide was required to reduce emergence, shoot weight, and shoot length. Overall, the results were similar to those of previous studies in which atmospheric oxygen was maintained in the headspace gas phase, demonstrating that the oxygen level in the headspace gas phase during mesocotyl emergence and early growth was not a significant factor in sulfide tolerance. Environ Toxicol Chem 2020;39:659–666. © 2020 SETAC